Problem Doktrin Relativisme (Studi Kritis Pemikiran Cendekiawan Muslim Indonesia) - Faisal Fauzi (Tasfiyah: Jurnal Pemikiran Islam, 2018)
This research tries to explain the doctrine of relativism which is obviously related to Sophists. The author explains its definition, concepts, and logical consequences it has if if this doctrine infiltrates "worldview" of a Muslim. It is revealed that a Muslim who was infiltrated by relativism virus would doubt any truth; that the truth cannot be achieved by human beings. It will be an absolute problem if relativism becomes a basis of the worldview of Muslim scholars especially in interpreting religious texts including al-Qur'an. This paper explains this problem including arguments to deny relativism which is adopted by several Muslim scholars today.